2022
DOI: 10.1177/13678779211061415
|View full text |Cite
|
Sign up to set email alerts
|

‘Generic visuals’ of Covid-19 in the news: Invoking banal belonging through symbolic reiteration

Abstract: In the early days of the Covid-19 pandemic, images of the virus molecule and ‘flatten-the-curve’ line charts were inescapable. There is now a vast visual repertoire of vaccines, people wearing face masks in everyday settings, choropleth maps and both bar and line charts. These ‘generic visuals’ circulate widely in the news media and, however unremarkable, play an important role in representing the crisis in particular ways. We argue that these generic visuals promote banal nationalism, localism and cosmopolita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Stock images promote particular-and sometimes skewed-ways of seeing, which are also part of a much broader set of social relations. Our focus here is not the contexts of production, distribution, and uptake that structure stock photography (see Aiello et al, 2022, for more on this), but rather the way these images work semiotically as they are circulated in the public arena of the (news) media. To be clear, we do not hold image banks solely responsible for clichéd or stereotypical ways of seeing; photographers and media agents making/using stock photos are necessarily also implicated.…”
Section: Critical Approaches To Stock Photographymentioning
confidence: 99%
“…Stock images promote particular-and sometimes skewed-ways of seeing, which are also part of a much broader set of social relations. Our focus here is not the contexts of production, distribution, and uptake that structure stock photography (see Aiello et al, 2022, for more on this), but rather the way these images work semiotically as they are circulated in the public arena of the (news) media. To be clear, we do not hold image banks solely responsible for clichéd or stereotypical ways of seeing; photographers and media agents making/using stock photos are necessarily also implicated.…”
Section: Critical Approaches To Stock Photographymentioning
confidence: 99%
“…The first report was about Corona vaccines. During the pandemic, data visualisations became abundant and simple charts were used to communicate quantitative information (Aiello et al, 2022). Bar charts are the most straightforward visualisation (Lankow et al, 2012) and are the best when comparing categories (Phetteplace, 2012).…”
Section: Types Of Data Visualisationsmentioning
confidence: 99%
“…Visuals are used to help frame issues ( Rodriguez & Dimitrova, 2011 ) and are known to influence how readers understand the salient issues of the day ( Saleem & Anderson, 2013 ). A steadily growing body of work has examined the media coverage of various aspects of the pandemic, and a small subsection of this work has examined the use and impact of visuals in contexts as varied as misinformation ( Brennen et al, 2021 ), use of data visualization ( Aiello et al, 2022 ), and daily news coverage in non-U.S. contexts ( Hubner, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings indicated that Asians were overrepresented in such images, and the author concluded that this pattern could add to the climate of xenophobia against Asians. Others such as Brennen et al (2021) examined the use of visuals in misinformation about the virus while Aiello et al (2022) analyzed how the U.K. media used stock photos and simple data visualizations to depict the pandemic in its early days. In a framing analysis of U.S. media, Hubner (2021) found that threat, economic consequences, and social consequences were the most prominent frames in the early days of the pandemic.…”
Section: Introductionmentioning
confidence: 99%